Commuting, Wages, and Household Behavior - José Ignacio Gimenez-Nadal; José Alberto Molina; Jorge Velilla (Institute of Labor Economics (IZA), 2024)
Commuting is a significant aspect of workers' daily routines and is associated with various negative outcomes. Traditional literature often models commuting from an urban perspective, focusing on the trade-off between commuting and housing. This paper offers an alternative view by using a household model as the theoretical basis to explore the interconnectedness of couples' commuting, wages, labor supply, and consumption. Using data from the PSID for the years 2011-2019, results indicate a positive and highly significant correlation between wages and commuting when analyzed cross-sectionally. However, changes in wages and commuting over an individual's life cycle are not related. Additionally, commuting appears to be associated with spousal commuting, household earnings, and wealth, while higher expenditures are linked to longer commutes, but again, only cross-sectionally.
Keywords: D12; D15; J22; J31; 330; commuting; household behavior; wages; PSID